KEMAMPUAN LITERASI MATEMATIS SISWA SMP DALAM MENYELESAIKAN SOAL PISA DITINJAU DARI GAYA BELAJAR VISUAL - Aulia Rohmatul Hidayah; Ikka Ananda Hakiki; Muhammad Faishal 'Afwi; Shofan Fiangga (Jurnal Karya Pendidikan Matematika, 2020)
The purpose of this study is to describe the mathematical literacy abilities of junior high school students in solving PISA questions in terms of visual learning styles. This type of research is a qualitative descriptive subject with three junior high school students who have different types of visual learning styles. Data collection was carried out with a learning style questionnaire and PISA test questions. The results of this study indicate that of the three research subjects obtained by one subject with pure visual learning style can solve all PISA questions on the three basic mathematical literacy abilities, namely in the formulate, employ, and interpret processes. Whereas subjects with visual-auditory learning styles and subjects with visual-kinesthetic learning styles have the same mathematical literacy abilities. Both subjects can solve PISA questions with the formulate and employ process categories, but cannot solve the questions in the interpret process.